Buddhist-Muslim Tolerance In Malang From 1998-2020 - Achmad Syarif; Ma'adul Yaqien Makkarateng (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2020)
Buddhist community in Malang is maintaining good relationship with other religious communities especially Muslim which are majority of Indonesia resident. Religious communities in Malang are very clever in maintaining tolerance so that religious diversity in Malang does not cause riots among religious people. Specifically, the researcher attempts to reveal the ingredients of tolerance between Buddhist and Muslim in this city so the other countries which face the problem of tolerance between religious communities should adopt from them. The researcher chose this region intentionally because it was the land of Buddhist growing in Indonesia along with the majority population of Muslim and limited the period from 1998-2020 because in this period the issues of tolerance arose significantly among Buddhist and Muslim and several interfaith activities were held to maintain Buddhist-Muslim harmony in this region.